2010
DOI: 10.1007/s10840-010-9530-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after catheter ablation for atrioventricular nodal reentrant tachycardia: a comparison of cryothermal and radiofrequency energy in a large series of patients

Abstract: BackgroundRadiofrequency (RF) catheter ablation for atrioventricular nodal reentrant tachycardia (AVNRT) is highly successful but carries a risk for inadvertent atrioventricular block. Cryoablation (cryo) has the potential to assess the safety of a site before the energy is applied.PurposeThe aim of this study was to evaluate the long-term efficacy and safety of cryothermal ablation in a large series of patients and compare it to RF.MethodsAll consecutive routinely performed AVNRT ablations from our centre bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 18 publications
2
45
0
Order By: Relevance
“…The overall long-term success rate using fluoroless cryoablation was 92% (24/26 procedures), similar to the success rate for RF ablation [33][34][35][36] . However, this result has been achieved performing a second fluoroless cryoablation procedure in 3 patients.…”
Section: Discussionsupporting
confidence: 54%
“…The overall long-term success rate using fluoroless cryoablation was 92% (24/26 procedures), similar to the success rate for RF ablation [33][34][35][36] . However, this result has been achieved performing a second fluoroless cryoablation procedure in 3 patients.…”
Section: Discussionsupporting
confidence: 54%
“…Before performing the electrophysiological study (EPS), the clinical diagnosis of typical AVNRT was based on the (1) history of a regular narrow complex tachycardia documented by electrocardiogram (ECG), Holter monitoring, transient arrhythmia monitoring, or other cardiac rhythm strip; (2) absence of identifiable P waves or presence of small terminal retrograde P waves that are not present in sinus rhythm 9 ; and (3) exclusion of manifest accessory pathway and/or other atrial tachycardias. Patients who had previously undergone any ablation procedures (with either source of energy) and those with structural heart disease were excluded from the present study.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Cryomapping (CM), performed by decreasing the temperature at the catheter tip to À301C, enables the assessment of functional electrophysiological effects of ablation before the execution of a permanent lesion. 4 In this way, the targeted site may be confirmed safe for ablation.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review that combined 22 published studies (including 2654 patients), cryothermal ablation had a high procedural success rate (95%; range, 85%-99%) that was comparable with RFCA (95%-98%). [30][31][32][35][36][37][38][39][40][41][42][43][44][45][46][47] Long-term freedom from recurrent arrhythmia with cryoablation was reported to be 89% (range, 81.3%-98%), which was lower than historical observations with RF (3%-7% recurrence). 32 Although historical comparisons between observational studies are fraught with potential biases, 11 comparative studies between cryothermy and RFCA for AVNRT (8 retrospective observational studies and 3 prospective randomized studies; Table 1), reported comparable acute success rates.…”
Section: Av Nodal Reentrant Tachycardiamentioning
confidence: 99%
“…32 Although historical comparisons between observational studies are fraught with potential biases, 11 comparative studies between cryothermy and RFCA for AVNRT (8 retrospective observational studies and 3 prospective randomized studies; Table 1), reported comparable acute success rates. [36][37][38][39][40][41][42][43][44][45][46][47] Although the longer term recurrence rate was statistically similar in 7 of the 11 studies, there was an overall trend that favored RFCA. Procedural duration was globally similar, with a shorter fluoroscopy time with cryoablation.…”
Section: Av Nodal Reentrant Tachycardiamentioning
confidence: 99%